1982
DOI: 10.1182/blood.v59.2.360.bloodjournal592360
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment for CFU-C from murine and human bone marrow using soybean agglutinin

Abstract: Mouse bone marrow and spleen cells agglutinated by soybean agglutinin (SBA) or peanut agglutinin (PNA) were previously shown to be enriched for spleen colony-forming cells (CFU-S) and sufficiently depleted of graft-versus-host reaction producing cells to allow hematologic reconstitution of lethally irradiated allogeneic recipient mice. A similar enrichment for cells capable of forming colonies in soft agar culture (CFU-C) has now been found in the SBA-agglutinated fraction of mouse bone marrow cells, in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The NALD cells were further enriched for putative stromal progenitors before MACS isolation as described (35,36) . Briefly, lectin‐binding cells were isolated by incubating with wheat germ agglutinin (WGA, Triticum vulgaris ; 1 mg/ml in PBS) for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The NALD cells were further enriched for putative stromal progenitors before MACS isolation as described (35,36) . Briefly, lectin‐binding cells were isolated by incubating with wheat germ agglutinin (WGA, Triticum vulgaris ; 1 mg/ml in PBS) for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We synthesized a novel material that allows separation of hematopoietic stem cells with SBA, which has multiple binding sites for sugar residues 1 . Reisner and coworkers 9 succeeded in reducing the occurrence of GVHD after allograft transplantation through selective depletion of T lymphocytes by mixing a core of galactose‐rich sheep RBCs with SBA. The sheep RBCs, however, were required for adhesion and separation, and this prevented satisfactory degrees of stability, safety, and utility 14 .…”
Section: Discussionmentioning
confidence: 99%
“…T‐lymphocyte depletion from marrow fluid can be achieved by mixing cells with sheep RBCs and SBA to form specific aggregates. This approach has facilitated successful marrow transplantation by expanding hematopoietic stem cells and reducing graft‐versus‐host disease (GVHD) 9 . Other trials have utilized a purging method with polystyrene culture devices carrying covalently immobilized SBA 10 …”
mentioning
confidence: 99%
“…When large numbers of patients with SCID were studied, we found that most did not have a fully MHC‐matched related donor who could provide a curative BMT (128–130). Consequently, Reisner from the Weizmann Institute in Rehovat, Israel, then a fellow in my laboratory, developed a method for treatment of SCID that used haploidentical T‐cell‐purged marrow as a life‐saving component of the treatment.…”
Section: Haploidentical T‐cell Purged Marrow Transplant As a Life‐savmentioning
confidence: 99%
“…Consequently, Reisner from the Weizmann Institute in Rehovat, Israel, then a fellow in my laboratory, developed a method for treatment of SCID that used haploidentical T‐cell‐purged marrow as a life‐saving component of the treatment. The marrow to be transplanted was purged of T cells by soybean agglutination (129) (enrichment of HSCs by the removal of unwanted T cells) using SRBC rosetting of T cells plus differential centrifugation (130). This treatment was, indeed, found to be effective and life‐saving, but not fully curative of the SCID, because although T cells and their functions were ultimately corrected, the correction occurred more slowly when a haploidentical T cell purged BMT was employed, as we had originally done (128, 130).…”
Section: Haploidentical T‐cell Purged Marrow Transplant As a Life‐savmentioning
confidence: 99%